Medan Makna Morfosemantik kata Auliya dalam Al-Qur’an: Kajian Semantik dengan Pendekatan Analisis Komponensial - Maksum Maksum; Tafiati Tafiati (Diwan: Jurnal Bahasa dan Sastra Arab, 2019)
This research aims to observethe terrain of morpho-semantic meaning of the word auliya’ in the Qur'an; what words are included in the morpho-semantic field of the word auliya’, and how the features are useful. This study aims to gather words that are in the morpho-semantic field of the auliya’ word 'in the Qur'an, find their meaning features, common components of the meaning and components of differentiating meaning (diagnostic communication) so that the meaning can be obtained representative of the word auliya'. The study found 234 words incorporated into the auliya’ 'morpho-semantic field' in 69 forms, spread over 55 letters in 208 verses. All these words come from six basic forms which are classified into three classes of words. The analysis reveals root meanings (general meaning components), i.e., ASSEMBLING, REDUCING, GOVERNING (action), NEAR / NO DISTANCE, HELP, FULL OF LOVE, RESPONSIBLE, ALWAYS SUPERVISING (characters) and distinguishing components, consisting of the meaning of the basic form, namely, GOD, KING / AUTHORITY / MASTER, RELIGION, HERITAGE OF HERITAGE, CULTURE (perpetrator), TIME AND INSTITUTION (etc.) and grammatical meaning, namely, Al-Syakhsh (pronoun), Al-'Adad (numeral) , Al-Ta'yin (definite) and Al-Nau '(gender), besides the meaning of' ‘time'specifically for the class of verb.